Validation and Adaptation of the HEALTHQUAL-KZ Questionnaire for Comprehensive Healthcare Quality Assessment in Public−Private Partnerships - Alimbetova, Maira S.; Kurakbaeyev, Kuralbai K.; Ismailov, Zhumagali K.; Baimuratova, Mairash A. (Calitatea Vieții, 2025)
The assessment of healthcare quality and patient satisfaction in public−private partnerships (PPPs) remains a critical but underexplored area, that has been identified as a priority by international health organizations. These metrics are essential for evaluating healthcare management models and shaping systems that meet population needs. This study aimed to develop a scientifically valid and culturally adapted version of the HEALTHQUAL questionnaire for Kazakhstan, based on the rigorous linguistic adaptation of the Portuguese version. Materials and Methods: The adaptation process involved translating the HEALTHQUAL-KZ questionnaire into Russian and Kazakh and then conducting a comprehensive validation process to ensure cultural and contextual relevance. To assess content and external validity, data from 100 randomly selected medical records were drawn from the integrated medical information system (MIS) at the Almaty Multidisciplinary Clinical Hospital, representing cases treated both three years before and three years after the PPP (Patient Protection Program) implementation. The adapted questionnaire’s reliability was confirmed through Cronbach’s alpha (α > 0.7) for internal consistency and Spearman’s rank correlation coefficient for test-retest reliability. These measures ensured the methodological robustness of the study. Results: The HEALTHQUAL-KZ questionnaire, which was validated, consists of 25 questions divided into five domains, demonstrated high reliability in all domains, as supported by Cronbach’s Alpha and Spearman’s rank correlation. The average completion time was approximately 12 minutes and 35 seconds. No significant correlation was found between demographic factors (age, education) and satisfaction levels, confirming the objectivity of the tool. Conclusion: This study presents the first validated adaptation of the HEALTHQUAL questionnaire for the healthcare context in Kazakhstan, offering a reliable instrument for assessing healthcare quality and patient satisfaction in PPP models. The significance of this research lies in its innovative methodological approach, providing a framework that can be transferred and adapted to other countries with similar healthcare systems and challenges. While it has local relevance, this work also contributes to the global discussion on improving healthcare through PPPs by offering a model for adapting healthcare quality assessment tools across cultures. This framework has the potential to standardize quality metrics and enable meaningful comparisons between diverse healthcare settings, advancing the field of healthcare research.